Bioscaffold Chitosan-Alginate For Tissue Engineering Applications - Suryati Suryati; Puspita S S; Meriatna Meriatna; Azhari Azhari (Faculty of Engineering, Malikussaleh University, 2018)
This study aims atexamining the condition of chitosan/alginate scaffold processing for tissue engineering applications. Chitosan 90.2% DD and Ca-alginate were both dissolved in 1% acetic acid and varied by volume ratios (v/v) (80:20, 70:30, 50:50, 30:70, 20:80) . The scaffold is printed to a glass mold, allowed to stand at room temperature for 24 hours, and thenheated in an oven at a temperature of 40oC for 48 hours. The outcome of this research product was in form of non-transparent thin sheets. FTIR test results revealed a number of peaks which indicated a certain level ofinteraction between chitosan, and Ca-alginate. The thermal degradation test established that there is a reduction in the melting point of the scaffold when there is a higher concentration in the material. It also indicated that there is an increase in the decomposition point in line with an increase in chitosan. Scaffold samples are physically superior as regards the easy handling of wet conditions (fixed shape and not easily torn), and providesunexpected results in aspects of biocompatibility.